48th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2010
DOI: 10.2514/6.2010-1566
|View full text |Cite
|
Sign up to set email alerts
|

Expansion Tube Investigation of Shock Stand-Off Distances in High-Enthalpy CO2 Flow Over Blunt Bodies

Abstract: The shock standoff distance in front of a blunt body is sensitive to the thermochemical state of the free stream. Recently, experimental and numerical studies have reported significantly different bow shock profiles in high-enthalpy carbon dioxide flows, a discrepancy that may result from non-equilibrium processes during flow acceleration in ground-based facilities. In this work, an expansion tube is used to create a Mach 5.7 carbon dioxide flow, matching the stagnation enthalpy and the velocity of previous st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The equation developed by Filippis provides the best prediction of the heat flux, with a 23% deviation in Air 4, a 26% deviation in Air 5, and a 35% deviation in Air 6. Though catalysis effects have been shown in the past to augment heat flux measurements in similar facilities, previous work in the HET has shown that catalytic effects are not expected to be an issue at these conditions [32].…”
Section: A Stagnation Point Resultsmentioning
confidence: 99%
“…The equation developed by Filippis provides the best prediction of the heat flux, with a 23% deviation in Air 4, a 26% deviation in Air 5, and a 35% deviation in Air 6. Though catalysis effects have been shown in the past to augment heat flux measurements in similar facilities, previous work in the HET has shown that catalytic effects are not expected to be an issue at these conditions [32].…”
Section: A Stagnation Point Resultsmentioning
confidence: 99%
“…Furthermore, the simulation of hypersonic flows is also a rather complex and difficult issue. Many researchers focused on the computational fluid dynamics, which is an efficient way to solve hypersonic problem (Farbar et al, 2013;Yih and Tahir, 2013;Sharma et al, 2010;James, 2006, 2008). Four-stage third-order implicit-explicit Runge-Kutta method, which represents a powerful tool for the time discretization of partial differential equations, can be applied to solve one-dimensional nonlinear equation (Ayati et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The HET condition was used by Sharma et al [111] [108] to study the shock standoff and surface heat transfer of various diameter sphere models and a scaled MSL model at various angles of attack.…”
Section: Shock Wave Comparisonmentioning
confidence: 99%